Early detection of nasopharyngeal carcinoma by plasma Epstein‐Barr virus DNA analysis in a surveillance program1. Issue 10 (21st February 2013) - Chan, K. C. Allen; Hung, Emily C. W.; Woo, John K. S.; Chan, Paul K. S.; Leung, Sing‐Fai; Lai, Franco P. T.; Cheng, Anita S. M.; Yeung, Sze Wan; Chan, Yin Wah; Tsui, Teresa K. C.; Kwok, Jeffrey S. S.; King, Ann D.; et al.
Abstract: BACKGROUND: Nasopharyngeal carcinoma (NPC) is prevalent in Southeast Asia. Over the last decade, plasma Epstein‐Barr virus (EBV) DNA has been developed as a tumor marker for NPC. In this study, the authors investigated whether plasma EBV DNA analysis is useful for NPC surveillance. METHODS: In total, 1318 volunteers ages 40 to 60 years were prospectively recruited. Plasma EBV DNA and serology for viral capsid antigen immunoglobulin A (IgA) were measured. Participants who had detectable plasma EBV DNA or positive IgA serology underwent nasal endoscopic examination and a follow‐up plasma EBV DNA analysis in approximately 2 weeks. All participants were followed for 2 years to record the development of NPC. RESULTS: Three individuals with NPC were identified at enrolment. All of them were positive for EBV DNA and remained positive in follow‐up analysis. Only 1 of those patients was positive for EBV serology. In 1 patient who had NPC with a small tumor confined to the mucosa, the tumor was not detectable on endoscopic examination. Because of a 2‐fold increase in plasma EBV DNA on the follow‐up analysis, that patient underwent magnetic resonance imaging, which revealed the tumor. Among the participants who did not have NPC but had initially positive plasma EBV DNA results, approximately 66% had negative EBV DNA results after a median of 2 weeks. CONCLUSIONS: Plasma EBV DNA analysis proved useful for detecting early NPC in individuals without a clinical suspicion of NPC. Repeating the test in those who had initially positive results differentiated those with NPC from those who had false‐positive results. Cancer 2013. © 2013 American Cancer Society. Abstract : This prospective study demonstrates that plasma Epstein‐Barr virus DNA is detectable in patients who have early stage nasopharyngeal carcinoma. The results indicate that it is feasible to use plasma Epstein‐Barr virus DNA as surveillance for nasopharyngeal carcinoma in asymptomatic individuals.